ʺIntroduction of a competent approach to healthcare in the system of higher educationʺ - Pyvovarov, O. (Problems of Engineer-Pedagogical Education, 2023)
In order to ensure the national security of the country, the introduction of the concept of healthcare into public life and, in particular, into the system of higher education is becoming increasingly important. An immediate and crucial objective involves fostering and ensuring the well-being of each individual, particularly those pursuing higher education. The research aims to scrutinize and assess the current state and methodologies involved in cultivating healthcare competence among students in higher education. The result is a generalization of the importance of the formation of healthcare competence of students of all educational specialties, in particular, medical and engineering. To determine the focus on the formation of healthcare competence in the context of the formation of general competences, a survey was conducted using the developed questionnaire through the creation of a Google form. Students of the first level of the 1st year of various higher education institutions of Kharkiv took part in the survey. The vast majority of students are satisfied with the quality of modern higher education. The diversity in responses highlights a broad spectrum of how students interpret learning outcomes. A substantial majority (72%) favored a definition of competence aligned with the National Qualifications Framework in terms of its components. Responses regarding the development of healthcare competence in higher education underscored the necessity for further comprehensive investigation. Employing competence-focused tasks has been acknowledged as a promising contemporary method for implementing the competence approach. Exploring ways to enhance pedagogical practices through technological support in shaping healthcare competence shows promise. The noticeable variations in how male and female higher education students perceive the existing state and pathways for developing this competence indicate the need for exploring gender-specific measures that should be taken into account.